The importance of the Pacific basin and APEC for Peru - Maúrtua de Romaña, Oscar (2024)
The Pacific Basin is considered one of the most important and dynamic geographic spaces on the planet. Made up of the main hegemonic powers and both developed and emerging economies, it is consolidated as an important geoeconomic source for its members. Through a rigorous analysis of academic sources, this article will address the reasons on which its importance is based, which are the main international organizations that have been created in said region - with special attention to APEC and the Pacific Alliance - as well as recommendations for the projection of Peruvian foreign policy in this area.